EMPLOYEE PERFORMANCE AFFECTED BY HUMAN INTELLIGENCE AND MEDIATED BY COMPETENCY - Juniarti, Atty; Setia, Bayu; Irwanti, Irwanti (TRIKONOMIKA, 2021)
This research begins with the discovery of problems in employee performance. The problem in this study is the low performance of employees, which is indicated by low human intelligence and competence. This study aims to analyze how the influence of human intelligence on employee performance is mediated by competence. With a sample of 90 people, using path analysis data analysis techniques (Path Analysis), the results show that emotional intelligence has a positive and significant effect on competence by 32.95%. Also, emotional intelligence has a positive and significant effect on performance mediated by competence of 15.88%. Then, intellectual intelligence has a positive and significant effect on competence by 22.49%, while intellectual intelligence has a positive and significant effect on performance mediated by competence by 12.77%. Furthermore, spiritual intelligence has a positive and significant effect on competence by 7.31%, and spiritual intelligence has a positive and significant effect on performance mediated by competence by 2.62%. Then competence has a positive and significant effect on employee performance by 73.44%.